Bacterial and fungal communities regulated directly and indirectly by tobacco-rape rotation promote tobacco production - Liu, Lu; Miao, Qi; Guo, Yingxin; Wang, Chen; Sun, Junwei; Fan, Zhiyong; Wang, Dexun; Hu, Yanxia; Li, Junying; Cui, Zhenling (Frontiers in Microbiology, 2024)
Tobacco continuous cropping is prevalent in intensive tobacco agriculture but often leads to microbial community imbalance, soil nutrient deficiency, and decreased crop productivity. While the tobacco-rape rotation has demonstrated significant benefits in increasing tobacco yield. Microorganisms play a crucial role in soil nutrient cycling and crop productivity. However, the internal mechanism of tobacco-rape rotation affecting tobacco yield through microbe-soil interaction is still unclear. In this study, two treatments, tobacco continuous cropping (TC) and tobacco-rape rotation (TR) were used to investigate how planting systems affect soil microbial diversity and community structure, and whether these changes subsequently affect crop yields. The results showed that compared with TC, TR significantly increased the Shannon index, Chao1 index, ACE index of bacteria and fungi, indicating increased microbial α-diversity. On the one hand, TR may directly affect the bacterial and fungal community structure due to the specificity of root morphology and root exudates in rape. Compared with TC, TR significantly increased the proportion of beneficial bacterial and fungal taxa while significantly reduced soil-borne pathogens. Additionally, TR enhanced the scale and complexity of microbial co-occurrence networks, promoting potential synergies between bacterial OTUs. On the other hand, TR indirectly changed microbial community composition by improving soil chemical properties and changing microbial life history strategies. Compared with TC, TR significantly increased the relative abundance of copiotrophs while reduced oligotrophs. Notably, TR significantly increased tobacco yield by 39.6% compared with TC. The relationships among yield, microbial community and soil chemical properties indicated that planting systems had the greatest total effect on tobacco yield, and the microbial community, particularly bacteria, had the greatest direct effect on tobacco yield. Our findings highlighted the potential of tobacco-rape rotation to increase yield by both directly and indirectly optimizing microbial community structure.